The Brain-Gut-Microbiome Axis: What Role Does It Play in Autism Spectrum Disorder? - Luna, Ruth Ann (Curr Dev Disord Rep, 2016)
The brain-gut-microbiome axis refers to the interactions between the central nervous system, gastrointestinal system, and microorganisms that live in the gastrointestinal tract. Exploring these interactions provides a rationale for why gastrointestinal disorders commonly occur in children with Autism Spectrum Disorders (ASD). Signs of altered brain-gut interactions that are closely associated with functional GI disorders (FGIDs) commonly occur in children with ASD. Studies of microbiome in ASD suggest that changes in the gut microbiome may be associated with ASD and with GI disorders in children with ASD. Further studies into the brain-gut-microbiome axis could lead to new techniques for identifying GI disorders in children with ASD and novel therapies for treating ASD behaviors.